Pengembangan Media Pembelajaran Berbasis Virtual Lab Pada Mata Pelajaran Resistor - Arrahman, Ravy Arif; Irsyadunas; Samudra, Ami Anggraini (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
The obstacles found in the basic subjects of computer network engineering and telecommunications, more specifically in the practicum on the use of network measuring instruments, the practicum is only carried out once a month due to the lack of facilities and infrastructure to carry out the practicum. So that students find it difficult to understand practicum material when studying. This study aims to produce valid and practical virtual lab learning media. This study used the Research and Development (R&D) method with the MDLC (Multimedia Development Life Cycle) development model. The number of subjects in this study amounted to 10 students as a sample. Data collection techniques using a questionnaire with a Likert scale. Data analysis techniques in the development of virtual lab learning media using Adobe Animate CC are quantitative data.The results of this research show that the average value of the validity test carried out by media experts is 0.85 in the valid category, while the value of the validity test by material experts is 0.84 in the valid category too. Meanwhile, in the practicality test on responses from teachers, results were obtained at 88.19% in the very practical category, and for responses from students, results were obtained at 82.88% in the very practical category. Based on assessments and input from media experts and material experts, as well as the results of field trials, it can be concluded that this interactive multimedia-based learning media has gone through good feasibility tests and is suitable for use as a basic learning tool for computer network and telecommunications techniques